Layered system architecture of remote robotic laboratory for real-time distant learning / Faisal Mahmud - Faisal , Mahmud (2022)
Laboratory experimental practice is an integral part of every day’s teaching and learning concerns in science and engineering courses. Under Industrial Revolution 3.0 schematic, the teaching of laboratory subjects has always been executed manually with the help of electrical instruments and data logging devices. Traditionally, a class full of students does not allow all participants to conduct laboratory exercises individually due to the minimal resources and time management. In this light, there is an urgent need to rejuvenate the current way of lab execution by injecting elements of Industrial Revolution 4.0 which centralizes internet tools coupled with the robotic system. Moreover, during an unprecedented time, such as the Covid-19 pandemic has enforced and proved a high demand to conduct laboratory experiments remotely by utilizing existing institutional online learning facilities. Therefore, working on laboratory exercises remotely via the server-based application may alleviate the difficulties in a traditional laboratory environment. In this research, a real-time online platform for performing lab exercises remotely has been proposed. This ‘Remote Robotic Laboratory’ would allow lab execution to be conducted remotely via an internet platform which promotes flexibility as well as brings more joy and excitement to the user. With this idea, the current project focuses on establishing a prototype of an online laboratory system that incorporates human interface software and hardware modules. The findings from our studies show that the proposed method was able to provide the students with a major increase in flexibility and performance. After the establishment of the system run time survey has been conducted with the help of students to evaluate the performance of the proposed facility. The investigation on the system response indicates good performance under different levels of internet bandwidth. The reliability of data recording was verified with the theoretical calculation which indicates a synchronized data transfer as low as 30ms interval. The survey on the user perception indicates more than 80% satisfaction over the concept.